ANALISIS IMPLEMENTASI NILAI – NILAI PENDIDIKAN KARAKTER PEDULI SOSIAL DALAM PEMBELAJARAN IPAS PADA GURU SEKOLAH DASAR - Sagita Ramadani; Rizki Ananda; Mufarizuddin; Yenni Fitra Surya; Yanti Yandri Kusuma (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the importance of instilling socially responsible character values ​​in learning to develop students with noble character. The purpose of this study was to determine how teachers implement socially responsible character values ​​in science and studies learning in elementary schools. This study used a descriptive qualitative method with data collection techniques through interviews, observation, and documentation. The results indicate that teachers have a good understanding of implementing socially responsible character values, such as empathy, mutual cooperation, and responsibility, through learning and school activities. Teachers consistently implemented habituation patterns, role models, and environmental conditioning strategies. However, obstacles remain, such as a lack of student self-confidence and the influence of a less than supportive family environment. The school has also attempted to address these obstacles through collaboration with parents and regular social activities. In conclusion, the implementation of socially responsible character values ​​in science and studies learning has been quite successful, although several aspects still require improvement.